1984
DOI: 10.1039/c39840000279
|View full text |Cite
|
Sign up to set email alerts
|

Sterically protected hemins with electronegative substituents: efficient catalysts for hydroxylation and epoxidation

Abstract: Meso-tetra(2,6-dichlorophenyl)porphinatoiron(iii) chloride and meso-tetra(pentachlorophenyl)porphinatoiron(iii) chloride, which resist y-0x0 dimer formation and oxidative destruction, are found to be unusually efficient catalysts for high-turnover, high-yield al kene epoxidation and alkane hydroxylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
3

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(84 citation statements)
references
References 2 publications
1
80
0
3
Order By: Relevance
“…30) Considering that the oxidation of piperine and piplartine occurs at the piperidine ring, the higher reactivity of piplartine must be related to the presence of the double bond, once it can stabilize by resonance the radical formed during the first of the metalloporphyrin-catalyzed oxidation. 31) It is also reported that in metalloporphyrin biomimetic reactions carried out in solvents as dichloroethane and acetonitrile, the oxidation of cyclohexane occur via this mechanism, leading to a predominant alcohol formation, [31][32][33][34][35] such as have occurred in the present work.…”
Section: Discussionmentioning
confidence: 80%
“…30) Considering that the oxidation of piperine and piplartine occurs at the piperidine ring, the higher reactivity of piplartine must be related to the presence of the double bond, once it can stabilize by resonance the radical formed during the first of the metalloporphyrin-catalyzed oxidation. 31) It is also reported that in metalloporphyrin biomimetic reactions carried out in solvents as dichloroethane and acetonitrile, the oxidation of cyclohexane occur via this mechanism, leading to a predominant alcohol formation, [31][32][33][34][35] such as have occurred in the present work.…”
Section: Discussionmentioning
confidence: 80%
“…Within 1 h of reaction time, the M nmTPP molecule was completely degraded. Even more robust por phyrins [22][23][24][25][26] such as the 'second-generation' ori/io-substituted chloro-porphyrins, and the penta-substituted chloro-and fluoro-porphyrins were either completely degraded during the course of the reaction or, in the case of M nmTpentaFPP, were unreactive. The reason for this fast oxidative degradation of the M nm por phyrin catalysts is most likely due to a rhodium -superoxo species that forms as a result of the interaction between the reduced rhodium bipyridyl complex and molecular oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…We chose M nmTPP complexes that are modified with electron-withdrawing substituents at the ortho positions in the phenyl rings as well as porphyrins with completely substituted phenyl rings. These so-called 'second genera tion' porphyrins [22][23][24][25][26] are less susceptible to attack at the meso-positions due to both steric effects from the substituents and the electronwithdrawing effect which makes the m eso-posi tion less favorable to electrophilic degradation. The results of epoxidation reactions carried out with these catalysts are shown in Table 2.…”
Section: Epoxidationmentioning
confidence: 99%
“…The microcosms were randomly set up in a 2 × 4 experimental block (6 times replicated) with 2 plant treatments (with and without maize plants) and 4 soil treatments: control soil (CT), compost-amended soil at 2 kg m -2 rate (COM), soil added with 1 g m -2 synthetic iron-porphyrin (POR), compostamended and iron-porphyrin-treated soil (COM+POR). The iron-porphyrin [meso-tetra(2,6-dichloro-3-sulfonatophenyl) porphyrinate of Fe(III)chloride], otherwise referred to as biomimetic catalyst, was synthesized according to the procedure of Traylor et al (1984) as modified by Piccolo et al (2005). The iron-porphyrin was surface-sprayed upon POR and POR+COM microcosms as a buffered solution (0.1 M phosphate buffer at pH 7.0) soon after soil filling.…”
Section: Experimental Set-upmentioning
confidence: 99%